Repeat annotation of Linum tenue - Fracassetti, Marco; Slotte, Tanja; Nystedt, Björn; Gutierrez-Valencia, Juanita; Berdan, Emma L.; Bunikis, Ignas; Soler, Lucile; Dainat, Jacques; Kutschera, Verena E.; Losvik, Aleksandra; Desamore, Aurelie; Hughes, P. William; et al. (Stockholm University, 2024)
The file contains the annotation for the repetitive regions in

Linum tenue

.

The detection of repeats has been done with RepeatMasker/RepeatModeler (https://www.repeatmasker.org/) using a custom repeat library.

The genome has been deposited to ENA with the accession id: GCA_946122785 (Project PRJEB52918). See link below.

It is part of this article Gutiérrez-Valencia, J., Fracassetti, M., Berdan, E. L., Bunikis, I., Soler, L., Dainat, J., ... & Slotte, T. (2022). Genomic analyses of the Linum distyly supergene reveal convergent evolution at the molecular level.

Current Biology

,

32

(20), 4360-4371. 10.1016/j.cub.2022.08.042

The file is in BED format converted with [BEDOPS](https://bedops.readthedocs.io/en/latest/content/reference/file-management/conversion/rmsk2bed.html). The fourth (Repeat class) and eleventh (Repeat name) columns have been reversed to highlight the Repeat name in the visualization.



Query sequence 1 chromosome

Query start 2 start

Query end 3 stop

Repeat class 4 id

Smith-Waterman score 5 score

Strand 6 strand

Percentage, substitutions 7

Percentage, deleted bases 8

Percentage, inserted bases 9

Bases in query, past match 10

Repeat name 11

Bases in complement of the repeat consensus sequence 12

Match start 13

Match end 14

Unique ID 15

Higher-scoring match (optional) 16
Keywords: Evolutionary ecology; Medical and Health Sciences; Medicin och hälsovetenskap; Ecology; Ekologi